Clinical researches of a specialized sports nutrition product "Hemosport" for the regulation of hemoglobin levels in adolescent girls who are professionally involved in sports - E. S. Tokaev; E. A. Nekrasov; I. S. Krasnova; A. A. Khasanov (National Electronic Information Consortium (NEICON), 2022)
The aim of the research was a clinical assessment of the effectiveness of the developed specialized sports nutrition product for regulating the level of hemoglobin in adolescent girls professionally involved in sports.Materials and methods: 23 girls - athletes of various sports specialization were researched during a training camp. The athletes were determined by the clinical parameters of blood, its general analysis and biochemical parameters, then the physical endurance and performance were assessed.Results: the developed product "Hemosport" demonstrated efficiency in most of the researched parameters in the main group compared with the control. The positive dynamics of most of the researched indicators revealed a general tendency to improve the state of vital organs and systems of the body of athletes of the main group, to increase their adaptive capabilities and vegetative balance.Conclusions: clinical studies of the specialized product "Hemosport" allow it to be recommended in the practice of sports nutrition for adolescent girls of 12-17 years old who are professionally involved in sports to compensate for iron deficiency nutritional deficiencies specific for this group of athletes, as well as to increase the efficiency and effectiveness of their training.